System Analysis and Design using Unified Modeling (UML) and Data Flow Diagram (DFD) - Rosziati Ibrahim; Norfaradilla Wahid; Norhanifah Murli; Hanayanti Hafit (2026)
This book introduces the analysis and design phase using object-oriented approach and structured-based approach. The use of examples with object-oriented approach and structured-based approach simplifies and reinforces the learning process. Each chapter presents examples to describe the concepts and elements of object-oriented approach and structured-based approach. For object-oriented approach, Unified Modeling Language (UML) specification diagrams, such as use case diagram, class diagram, sequence diagram and activity diagram, are used in case studies. For structured-based approach, Data Flow Diagram (DFD) specification diagrams, such as context diagram, data flow diagram, entity relationship diagram and flowchart, are used in case studies. The case studies were designed to support the essential topics discussed in the respective chapters.This book consists of 6 chapters. Chapter 1 attempts to introduce the system development life cycle (SDLC) and its phases. Chapter 2 introduces rules for object-oriented approach and Chapter 3 covers the case studies using UML. Chapter 4 discusses rules for structured-based approach and Chapter 5 presents the case studies using DFD. Finally, Chapter 6 discusses the similarities and differences between UML and DFD. Each chapter includes- Learning outcomes to alert readers with the content.- Examples to demonstrate how the concepts of object-oriented approach and structured-based approach are implemented for the diagrams.